Fluoroquinolone-induced bilateral rupture of the Achilles tendon: clinical and sonographic findings - E. Filippucci; A. Farina; F. Bartolucci; C. Spallacci; P. Busilacchi; W. Grassi (PAGEPress Publications, 2003)
The fluoroquinolones are antibiotics widely used in the clinical practice. The concomitant use of corticosteroids and fluoroquinolones in elderly patients is recognised as a risk factor for developing clinically relevant tendon lesions. Fluoroquinolone-induced tendinopathy is underreported in the literature. Clinical case. A 67-year-old man, came to our observation complaining of 5 days history of bilateral heel pain. The patient had a medical history of sarcoidosis and was treated with a daily dose of 5 mg of prednisone. He was initially given oral levofloxacin (500 mg/die) for 10 days, because of an acute respiratory infection. Two days before the end of the antibiotic therapy, he developed bilateral heel pain. He denied any history of trauma. Physical examination revealed swelling and marked tenderness with mild palpation of the Achilles tendons at the calcaneal insertion. The ultrasound evaluation of the Achilles tendons revealed the following main abnormalities: diffuse thickening, loss of the "fibrillar" echotexture, blurred margins, and bilateral partial tendon tears. Discussion. Bilateral Achilles tendon pain and rupture has been described as a rare adverse effect of fluoroquinolone treatment. Most of the fluoroquinolone-induced tendinopathies of the Achilles tendon are due to ciprofloxacin. To the best of our knowledge, this is the first description of bilateral Achilles tendon rupture due to levofloxacin. The risk/benefit ratio of the fluoroquinolones should be carefully considered and these drugs should be prescribed cautiously in elderly patients treated with corticosteroids. This case can be regarded as a representative example of the potential clinical efficacy of sonography in daily rheumatological practise.